Thermo-dynamic Parameter Calculation of Refrigerant and Numerical Simulation of Refrigerant Cold Plate - WANG Xingzhi; WANG Xiong; LI Yanyong; YAO Lei; WANG Zhongzan; WANG Weijie (Kongzhi Yu Xinxi Jishu)
Owing to the characteristics of low thermal resistance and high latent heat for refrigerant boiling heat transfer, refrigerant cold plate plays a very important role in heat dissipation of high power electronic devices. Based on Cleland model and element model, it proposed a calculation method of thermo-dynamic parameter for the friction of copper pipe, and then substituted in Fluent as thermal boundary condition via UDF(user defined functions) to calculate the temperature field of refrigerant cold plate. Comparison between simulation and experimental results shows that this method has high accuracy.